Stress-Related Gene Expression in Liver Tissues from Laying Hens Housed in Conventional Cage and Cage-Free Systems in the Tropics - María Paula Herrera-Sánchez; Roy Rodríguez-Hernández; Iang Schroniltgen Rondón-Barragán (Veterinary Medicine International)
Global egg production is mainly based on cage systems, which have been associated with negative effects on the welfare of birds. Stress factors in restrictive production systems can lead to changes in gene transcription and protein synthesis, ultimately impacting the quality of poultry products. The liver serves various metabolic functions, such as glycogen storage, and plays a crucial role in animals’ adaptation to environmental changes. Consequently, both internal and external conditions can influence liver functions. The aim of this study was to evaluate the gene expression of AGP, CRP, NOX4, SOD1, CAT, GPX1, SREBF1, and FXR in the liver of laying hens under two different production systems. Liver tissues from Hy-Line Brown hens housed in conventional cage and cage-free egg production systems at 60 and 80 weeks of production were used. mRNA transcript levels were determined by qPCR using the relative quantification method and ACTB as the reference gene. AGP, SOD1, and SREBF1 gene expressions were significantly higher in the conventional cage group at the 60 weeks of production. Furthermore, the mRNA levels of transcripts related to oxidative stress and lipid metabolism were higher in the group of laying hens housed in conventional cages compared to those in cage-free systems. These results suggest differential gene expression of genes related to oxidative stress in liver tissues from hens housed in conventional cages compared to cage-free systems. The conditions of the egg production system can impact the gene expression of oxidative stress and lipid synthesis genes, potentially leading to changes in the metabolism and performance of hens, including egg quality.